PELAKSANAAN INOVASI PELAYANAN PERIZINAN OLEH DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA PEKANBARU TAHUN 2016-2017 - Julianto, M. Irvan; Wicaksono, Baskoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Pekanbaru City Investment and One-Stop Services (DPM-PTSP) is a Regional Work Unit which is a supporting element of the Mayor's duties in the field of licensing and non-licensing services with the main task of carrying out part of regional government affairs in the licensing and non-licensing services in an integrated manner. To that end, in organizing the Pekanbaru City PTSP DPM-licensing service seeks to prepare the capacity of reliable (professional, tested and trusted) institutions and apparatus through innovations carried out to achieve service objectives in the licensing sector. However, the licensing service innovation is not as expected, where there are business actors who do not have permits / legality to run a business, also thousands of warehouse units that do not have a Warehouse Registration in Pekanbaru City (Source; www.riausky.com, reported Tuesday, August 30, 2016). The research objective was to determine the implementation of licensing service innovations and the factors that hinder the implementation of service innovation by the Pekanbaru City PTSP DPM in 2016-2017. The research method used is descriptive qualitative method with data collection instruments including interviews, documentation studies related to research objectives, with the research instruments used referring to the innovation theory proposed by Suwarno (2008) that innovation in public services is born in the form and initiative / methods that include partnerships in the delivery of public services, the use of information and communication technology in public services, and the procurement or establishment of service institutions. The results of the research on the implementation of licensing service innovations by Pekanbaru City DPM-PTSP from the side of the implementation of the use of technology in licensing service delivery have been running optimally. However, partnership efforts have not been effective to reach the target groups of business actors with the participation of small-medium scale business capital, where partnerships and procurement / establishment of "mobile car" services aim to socialize and manage licensing services that are easy, fast and inexpensive by "connecting" Sub-district government apparatus in Pekanbaru City are temporary (unsustainable, massive and scheduled to business actors, especially small and medium scale business actors).Keywords : Public Service, Service Innovation, Service Information Technology